Analysis of Interstitial Saturation in and Entrainment From Gas-Liquid Separation Media - Golkar Fard, Vahid (Curtin University, 2020)
This thesis developed a methodology in order to compare the performance of different types of coalescing filters (fibrous, knitted, and foam media) which has not been reported in literature. Moreover, the local optimum in pressure drop curve which identified in this work is a novel contribution to the field of interfacial science and gas-liquid separation which can significantly affect the coalescence filters design in future.